Chest Compression Fraction in Simulated Cardiac Arrest Management by Primary Care Paramedics: King Laryngeal Tube Airway Versus Basic Airway Management. (6th March 2013) - Jensen, Jan L.; Walker, Mark; LeRoux, Yves; Carter, Alix
Abstract Objective. The objective of this randomized simulation study was to determine whether use of the King laryngeal tube (KLT) airway resulted in differences in chest compression fraction (CCF) during simulated cardiac arrest managed by primary care paramedics (PCPs), as compared with basic airway management (bag–mask ventilation [BMV]). Methods. The KLT was introduced to all providers in our system at the time of study initiation. All participants received the same training, and were not aware that the primary outcome of the study was CCF. Standard airway management by PCPs prior to this was BMV. Pairs of PCPs were randomized to use KLT or BMV during a scripted 6-minute cardiac arrest scenario. The scenarios were videotaped, and data were abstracted by a single investigator. The CCF was calculated (fraction of time chest compressions were done/total scenario time). The CCF, number of seconds to first ventilation, and number of seconds to first compression were compared using the Mann-Whitney U test. Results. Sixty-seven pairs of PCPs participated: 30 in the KLT arm and 37 in the BMV arm. Demographics were similar in each group: KLT 68.3% males, BMV 55.4% males; KLT mean age 33.52 years (standard deviation [SD]: 11.95), BMV mean age 32.07 years (SD: 8.78); and KLT mean years of experience 9.03 (SD: 9.86), BMV mean years of experience 6.59 (SD: 6.58). The CCF was higher in the KLT group: median 0.82 (interquartile range [IQR] 0.71–0.88) compared with the BMV group: median 0.70 (IQR 0.66–0.73), p < 0.001. Time to first ventilation was longer in the KLT group: median 83.00 sec (IQR 43.75–139.25 sec) than in the BMV group: median 48.00 sec (IQR 37.00–71.00 sec), p = 0.004. Times to first compression were similar: KLT median 13.00 sec (IQR 8.00–17.00 sec), BMV median 14.00 sec (IQR 11.00–18.50 sec), p = 0.331. Conclusion. In this randomized simulation study, KLT use by PCPs during simulated standard cardiac arrest scenarios was found to significantly increase CCF compared with basic airway management with BMV. Key words: emergency medical services; paramedics; airway; extraglottic airway device; cardiac arrest